THE CHLORINE NEEDS OF COCONUTS - S.S. Magat; R.Z. Margate (International Coconut Community, 1990)
A study designed to determine the nutritional needs of coconut from nursery to full‑bearing was conducted from 1974 to 1988 in a Cl-deficient soil (Topic Tropudalf) of Davao, Southern Philippines. At nursery stage, only chlorine application improved the growth of the seedlings based on girth size which was highly correlated with increased leaf Cl. During the first five years in the field, K and Cl significantly influenced the growth of the palms which were positively correlated to ail growth parameters, i.e. girth, number of leaflets, living fronds and leaf production. During the fifth year, Cl‑fertilization resulted in 115% more flowering palms than the unfertilized ones. From then on, Cl application consistently increased nut production, copra weight per nut and copra yield per tree which was correlated with leaf Cl. However, the positive effects of other nutrients like N, K and Mg on yield as well as interaction effects were inconsistent over the years. The nutritional needs of palms for Cl at the nursery stage is 30 g Cl per seedling. Under field condition, the requirement increases with age from 40 g to 1,000 g per palm leveling off at fifth year from planting.